Associations of obesity with modifiable risk factors for the development of cardiovascular disease in patients with rheumatoid arthritis. Issue 2 (3rd August 2008) - Stavropoulos-Kalinoglou, A; Metsios, G S; Panoulas, V F; Douglas, K M J; Nevill, A M; Jamurtas, A Z; Kita, M; Koutedakis, Y; Kitas, G D
Abstract : Objectives: To assess the association of body mass index (BMI) with modifiable cardiovascular disease (CVD) risk factors in patients with rheumatoid arthritis (RA). Methods: BMI, disease activity, selected CVD risk factors and CVD medication were assessed in 378 (276 women) patients with RA. Patients exceeding accepted thresholds in ⩾3 CVD risk factors were classified as having the metabolic syndrome (MetS). Results: BMI independently associated with hypertension (OR = 1.28 (95% CI = 1.22 to 1.34); p = 0.001), high-density lipoprotein (OR = 1.10 (95% CI = 1.06 to 1.15); p = 0.025), insulin resistance (OR = 1.13 (95% CI = 1.08 to 1.18); p = 0.000) and MetS (OR = 1.15 (95% CI = 1.08 to 1.21); p = 0.000). In multivariable analyses, BMI had the strongest associations with CVD risk factors (F1–354  = 8.663, p = 0.000), and this was followed by lipid-lowering treatment (F1–354  = 7.651, p = 0.000), age (F1–354  = 7.541, p = 0.000), antihypertensive treatment (F1–354  = 4.997, p = 0.000) and gender (F1–354  = 4.707, p = 0.000). Prevalence of hypertension (p = 0.004), insulin resistance (p = 0.005) and MetS (p = 0.000) was significantly different between patients with RA who were normal, overweight and obese, and BMI differed significantly according to the number of risk factors present (p = 0.000). Conclusions: Increasing BMI associates with increased CVD risk independently of many confounders. RA-specific BMI cut-off points better identify patients with RA at increased CVD risk. Weight-loss regimens should be developed and applied in order to reduce CVD in patients with RA.